Comparison of Telephone and Video Telehealth Consultations: Systematic Review - Oyungerel Byambasuren; Hannah Greenwood; Mina Bakhit; Tiffany Atkins; Justin Clark; Anna Mae Scott; Paul Glasziou (JMIR Publications, 2023)
BackgroundTelehealth has been used for health care delivery for decades, but the COVID-19 pandemic greatly accelerated the uptake of telehealth in many care settings globally. However, few studies have carried out a direct comparison among different telehealth modalities, with very few studies having compared the effectiveness of telephone and video telehealth modalities. ObjectiveThis study aimed to identify and synthesize randomized controlled trials (RCTs) comparing synchronous telehealth consultations delivered by telephone and those conducted by video with outcomes such as clinical effectiveness, patient safety, cost-effectiveness, and patient and clinician satisfaction with care. MethodsPubMed (MEDLINE), Embase, and CENTRAL were searched via the Cochrane Library from inception until February 10, 2023, for RCTs without any language restriction. Forward and backward citation searches were conducted on included RCTs. The Cochrane Risk of Bias 2 tool was used to assess the quality of the studies. We included studies carried out in any health setting-involving all types of outpatient cohorts and all types of health care providers-that compared synchronous video consultations directly with telephone consultations and reported outcomes specified in the objective. We excluded studies of clinician-to-clinician telehealth consults, hospitalized patients, and asynchronous consultations. ResultsSixteen RCTs-10 in the United States, 3 in the United Kingdom, 2 in Canada, and 1 in Australia involving 1719 participants-were included in the qualitative and quantitative analyses. Most of the telehealth interventions were for hospital-based outpatient follow-ups, monitoring, and rehabilitation (n=13). The 3 studies that were conducted in the community all focused on smoking cessation. In half of the studies, nurses delivered the care (n=8). Almost all included studies had high or unclear risk of bias, mainly due to bias in the randomization process and selection of reported results. The trials found no substantial differences between telephone and video telehealth consultations with regard to clinical effectiveness, patient satisfaction, and health care use (cost-effectiveness) outcomes. None of the studies reported on patient safety or adverse events. We did not find any study on telehealth interventions for diagnosis, initiating new treatment, or those conducted in a primary care setting. ConclusionsBased on a small set of diverse trials, we found no notable differences between telephone and video consultations for the management of patients with an established diagnosis. There is also a significant lack of telehealth research in primary care settings despite its high uptake.